2016
DOI: 10.1093/glycob/cww089
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan synthase control of synthesis rate and hyaluronan product size are independent functions differentially affected by mutations in a conserved tandem B-X7-B motif

Abstract: Hyaluronan synthases (HAS) normally make large (>MDa) hyaluronan (HA) products. Smaller HA fragments (e.g. 100-400 kDa) produced in vivo are associated with inflammation and cell signaling by HA receptors that bind small, but not large, HA. Although HA fragments can arise from breakdown by hyaluronidases, HAS might also be regulated directly to synthesize small HA. Here we examined the Streptococcus equisimilis HAS (SeHAS) C-terminus, which contains a tandem B-X 7 -B motif (K 398 -X 7 -R 406 -X 7 -K 414 ), by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 73 publications
2
24
0
Order By: Relevance
“…In physiological conditions, HAS1 and HAS2 synthesize HA polymers of high molecular mass, while HAS3 synthesizes shorter HA polymers (24), and the production of low molecular mass HA can be obtained by the action of degrading enzymes as well as by oxidative stress or ultraviolet light (25,26). Interestingly, the stoichiometry of the cytosolic UDP substrates has a critical role to define HA polymer length, and the C-terminal region of HASes appears to have regulatory functions (27).…”
Section: Hyaluronanmentioning
confidence: 99%
“…In physiological conditions, HAS1 and HAS2 synthesize HA polymers of high molecular mass, while HAS3 synthesizes shorter HA polymers (24), and the production of low molecular mass HA can be obtained by the action of degrading enzymes as well as by oxidative stress or ultraviolet light (25,26). Interestingly, the stoichiometry of the cytosolic UDP substrates has a critical role to define HA polymer length, and the C-terminal region of HASes appears to have regulatory functions (27).…”
Section: Hyaluronanmentioning
confidence: 99%
“…Similarly, it has been shown that the catalytic activity of β‐1,4‐galactosyltransferase is modulated by the conformational change brought forth by its two flexible loops . Interestingly, T40L is a part of the HAS tandem‐motif region described to be involved in both the control of HA synthesis rate and the control of HA size for class I seHAS . Furthermore, MD simulations show that the increase in flexibility caused by the substitutions results in the N‐terminal region first interacting with the GlcNAc‐transferase and then turning towards the GlcA‐transferase domain of pmHAS (Figures B and S8).…”
Section: Discussionmentioning
confidence: 93%
“…The protein structure of GlmU was previously studied in E. coli, and the catalytic site of this protein was also matched to the variable binding regions predicted from the P. multocida strains in this study. These variable regions correlated with N-terminal pyrophosphorylase and C-terminal acetyltransferase catalytic sites [39,40]. GlmU has two active sites: (i) acetyltransferase, which is responsible for CoA-dependent acetylation of D-glucosamine-1-P to N-acetyl-D-glucosamine-1-P at the C-terminal domain, and (ii) pyrophosphorylase, which catalyses the transfer of uridyl from UTP to D-glucosamine-1-P, forming UDP-N-acetyl-D-glucosamine and pyrophosphate at the N-terminal domain [40].…”
Section: Discussionmentioning
confidence: 96%